2007
DOI: 10.1161/circulationaha.106.627265
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Chronic Chagas Disease

Abstract: Background-Chagas disease is a major cause of morbidity and mortality in Latin America. Knowledge of the predictors of prognosis can help clinical decision making by identifying patients' level of risk. Methods and Results-We reviewed the published literature on prognostic factors in patients with Chagas disease by performing a PubMed search for articles published in any language between 1985 and February 2006 and hand searches of the reference lists of retrieved articles. Studies were selected if they include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
2
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 278 publications
(150 citation statements)
references
References 32 publications
4
131
2
10
Order By: Relevance
“…Rassi Jr. et al 13 performed a systematic literature review regarding predictors of mortality in patients with Chagas heart disease. By analyzing clinical trials published between 1985 and 2006, these authors found that impaired left ventricular function, NYHA functional class III or IV, cardiomegaly, and nonsustained ventricular tachycardia are associated with poor prognosis in patients with chronic Chagas disease.…”
Section: Discussionmentioning
confidence: 99%
“…Rassi Jr. et al 13 performed a systematic literature review regarding predictors of mortality in patients with Chagas heart disease. By analyzing clinical trials published between 1985 and 2006, these authors found that impaired left ventricular function, NYHA functional class III or IV, cardiomegaly, and nonsustained ventricular tachycardia are associated with poor prognosis in patients with chronic Chagas disease.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, we published the first systematic review integrating the results of all studies on the chronic phase of Chagas disease that used multivariable regression models of prognosis and analysed a clearly defined outcome, such as all-cause mortality, sudden cardiac death or cardiovascular death (Rassi Jr et al 2007). From 606 potentially relevant studies published between 1985-2006, 12 articles met the inclusion criteria and were thereby selected for analysis (Espinosa et al 1991, Hagar & Rahimtoola 1991, Bestetti et al 1994, 1996, Carrasco et al 1994, Mady et al 1994, Garzon et al 1998, Rodriguez-Salas et al 1998, Leite et al 2003, Salles et al 2003, Viotti et al 2004, Rassi Jr et al 2006).…”
Section: Prognostic Factors and Risk Stratificationmentioning
confidence: 99%
“…First, 20% to 30% of Chagasic patients complain of chest pain resembling angina in location and character, but without relationship to effort and unrelieved by organic nitrates (Punukollu et al, 2007). Second, electrocardiograms of many patients show typical findings of ischemia, such as ST-T changes and abnormal Q waves (Bern et al, 2007;Punukollu et al, 2007;Rassi et al, 2007). However, coronary angiography in Chagas cardiomyopathy invariably demonstrates the absence of obstructive coronary disease (Marin-Neto et al, 2007;Torres et al, 1995).…”
Section: Microvascular Abnormalities and Ischemiamentioning
confidence: 99%